METHOD OF MEASURING MECHANICAL PROPERTIES OF COATED FABRIC USING PHOTOGRAMMETRY TECHNIQUES - Navneet Kumar , Kewal Singh, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
A rapid growth is reported in the demand of the materials that are very flexible and easy to handle. Other than that people like to buy such kind of materials that do not require a lot of space and perform rapid deployment. This is because these type of materials are quite durable and have low maintenance cost. The fiber waste materials like the coated fibers are quite important in today’s world. These things are being used in different type of industries and applications such as technical textiles, geotextiles, beauty care products and many health care products. There are many short and intelligent electronic applications that also use these fibers. Coated fabric is very useful in the places where you need a product which behaves like a stretched membrane. It is also suggested by different type of studies that there is no bending in the coated fabric. That is the main reason they provide great strength and metallic properties at various places. If anyone want to examine the mechanical properties of the coated fabric then there is a special paper which is very helpful in this procedure. It is very required to find out the mechanical properties of fabric for getting the information about the software. People will be able to get the different type of information related to the photogrammetry techniques and material testing equipment in this paper. These photogrammetry techniques are very helpful for recording different type of linear and angular displacement data which is caused due to the uniaxial and biaxial tension. There are different type of tests that are used in this procedure such as a Young's modulus and Poisson’s ratio. The results that are provided by the photogrammetry method are completely equal to the results obtained from the tensile testing machine. It is very helpful in getting the information about the stress shear strain behavior. These values are obtained with the help of bias tension test. The paper will provide different type of information related to the testing that is very helpful in getting the mechanical properties of a coated fabric.